ENVIRONMENTAL MANAGEMENT AND SUSTAINABILITY: A STUDY OF CASES MULTIPLE ON SECTOR HOTEL BY JOÃO PESSOA/PB. - Felix, Vagner Souza de; Santos, Joel Silva dos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707855 This article seeks to identify the various environmental management practices adopted by some of the hotel chain hotels in Joao Pessoa, PB. The paper discusses the importance of the adoption of Environmental Management System for the materialization of environmental sustainability in this segment. The research also aims check the main environmental impacts generated by the hotels investigated, as well as, social and environmental profiling of the same, with respect to the use of natural resources and environmental sustainability. For the research, was originally done a bibliographic about the topic in question, followed by a documentary research bodies in to verify compliance with environmental legislation by the companies investigated. It was also carried out a questionnaire theme and technical visit in order to certify the survey information. Thus, it was found that the hotel sector of the city of João Pessoa, still lacks environmental management practices that enable the sustainable use of various natural resources.